The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/2053-1591/ab8a83
|View full text |Cite
|
Sign up to set email alerts
|

Biosorbents prepared from pomelo peel by hydrothermal technique and its adsorption properties for congo red

Abstract: A new kind of biosorbent was prepared from pomelo peel by using potassium hydroxide as activating agent and hydrothermal treatment method. The characteristics of materials were analyzed by SEM, BET and FTIR. Increasing the adsorbent dosage (from 2.5 to 17.5 g l −1 ) and contents of congo red in solution (from 20 to 50 mg l −1 ) cause the increment of removal rate of congo red. On the other side, the removal rate is decrement with rising of temperature and pH. The maximum adsorption quantity of biosorbent was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 66 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…For copper removal, different studies proved that surface charge, pH and adsorbent dosage were the main parameters affecting the adsorption capacity, while for lead superior efficiency (>99.5%) was achieved with Ni/Fe-doped hydrochar [125]. Additionally, organic compounds like methylene blue, methyl orange and Congo red were removed from contaminated solutions through the adsorption on hydrochar produced from biomass waste [126][127][128][129][130][131][132]. Up to 655.7 mg of methylene blue for each gram of hydrochar was absorbed when bamboo sawdust was carbonized into 1 M hydrochloric acid solution, before being further treated with NaOH for 1 h. Acid modification led to 100%-200% increase in the adsorption capacity when the solution was kept in the pH range of 10-12 [127].…”
Section: Adsorption Of Contaminantsmentioning
confidence: 99%
“…For copper removal, different studies proved that surface charge, pH and adsorbent dosage were the main parameters affecting the adsorption capacity, while for lead superior efficiency (>99.5%) was achieved with Ni/Fe-doped hydrochar [125]. Additionally, organic compounds like methylene blue, methyl orange and Congo red were removed from contaminated solutions through the adsorption on hydrochar produced from biomass waste [126][127][128][129][130][131][132]. Up to 655.7 mg of methylene blue for each gram of hydrochar was absorbed when bamboo sawdust was carbonized into 1 M hydrochloric acid solution, before being further treated with NaOH for 1 h. Acid modification led to 100%-200% increase in the adsorption capacity when the solution was kept in the pH range of 10-12 [127].…”
Section: Adsorption Of Contaminantsmentioning
confidence: 99%
“…The pore size distribution of TAC (the inset of Figure 3 b) consists of limited micropores and mesopores; the corresponding textural characteristics are summarized in Table 1 . The TAC displays extremely low porosity with a specific surface area of 5 m 2 g −1 and a pore volume of 0.034 cm 3 g −1 , which are similar to those of products derived from other types of biowaste [ 32 , 38 , 39 ]. By increasing the KOH agent, the specific surface area notably increases from 2143 m 2 g −1 to 2235 m 2 g −1 and then decreases to 2206 m 2 g −1 .…”
Section: Resultsmentioning
confidence: 92%
“…These further confirmed that the adsorption process was not unfavorable at higher temperature. 54,55 3.3. Reusability assessments Fig.…”
Section: Adsorption Experimentsmentioning
confidence: 99%